First-year undergraduate ESP students Virtual Reality User Experience - Christoforou, Maria; Boglou, Dimitrios; Xerou, Eftychia (My University, 2019)
For the last decade, a plethora of e-tools has permeated and proliferated throughout various educational institutions and classrooms. English for Specific Purposes (ESP) classrooms at the Cyprus University of Technology (CUT) were no exception. CUT ESP instructors have embraced these new and ever-evolving e-tools and implemented them into their classrooms in order to transform and enhance their students’ learning experience (Constantinou, 2018) whereas notable positive impacts in ESP classes have been highlighted on a global scale (Bloch, 2013). The adoption of e-tools in classrooms has not been an easy task for instructors, ESP instructors included. Problems such as lack of infrastructure, lack of training, lecturers’ inexperience with technology as well as inadequate technical support have constituted inhibiting factors for using technology in the classroom. Based on the aforementioned adaptations, this pilot study aims to capture the User Experience (UX) of 14 first-year undergraduate ESP students in Virtual Reality, as an innovative technological tool, in order to determine whether to implement it in the ESP teaching context. The study uses the collection of qualitative data through the conduct of semi-structured interviews in order to investigate further the experience of students with VR.
Keywords: FLL (Foreign Language Learning); Virtual Reality (VR); English for Specific Purposes (ESP); Tertiary education